2022
DOI: 10.3390/nu14102147
|View full text |Cite
|
Sign up to set email alerts
|

Satiety of Edible Insect-Based Food Products as a Component of Body Weight Control

Abstract: Among the many aspects determining the nutritional potential of insect-based foods, research into the satiating potential of foods is an important starting point in the design of new functional foods, including those based on edible insects. The aim of this study was to assess the satiating value of products with the addition of freeze-dried insect flour. The test material included wheat pancakes in which corresponding proportions of wheat flour were substituted with 10% Mw, 0% Mw, and 30% Mw of flour from fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 63 publications
0
19
1
Order By: Relevance
“…Adebowale et al (2005) concluded that the African giant cricket would be suited for foods requiring gelling and thickening, foods where water retention is desirable during cooking, and good for food products involving fat absorption such as bakery products. Research regarding the enrichment of foods with insect proteins has found them to be promising additives for the improvement of the nutritional profile and satiety potential of foods (Kowalski et al, 2022a; Skotnicka et al, 2022). Supplementation of gluten‐free bread with cricket powder led to an improvement in the free amino acid profile due to an increased level of pyrazines found in the enriched bread (Wieczorek et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Adebowale et al (2005) concluded that the African giant cricket would be suited for foods requiring gelling and thickening, foods where water retention is desirable during cooking, and good for food products involving fat absorption such as bakery products. Research regarding the enrichment of foods with insect proteins has found them to be promising additives for the improvement of the nutritional profile and satiety potential of foods (Kowalski et al, 2022a; Skotnicka et al, 2022). Supplementation of gluten‐free bread with cricket powder led to an improvement in the free amino acid profile due to an increased level of pyrazines found in the enriched bread (Wieczorek et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, edible insects may not only diversify the daily diet, contribute to food and nutritional security, but also have an impact on the reduction of the carbon footprint compared to the production of protein from farm animals [Vauterin et al, 2021]. Edible insects are known to be of use in variety of food products, including cricket powder for the production of muffin [Pauter et al, 2018]; Hermetia illucens, Acheta domesticus, Alphitobius diaperinus and Tenebrio molitor flours for bakery products [González et al, 2019;Kowalski at al., 2022;Wu et al, 2020], A. diaperinus and A. domesticus for pancakes [Skotnicka et al, 2022] as well as mealworm larvae as a meat substitute in the production of hamburgers [Megido et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 14 studies were included in the systematic analysis. Nine studies were randomized controlled trials (RCT), with the consumption of insect-based meals as the test product [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] ( Table 1 ). The other five studies addressed allergenicity ( Table 2 ): one was a patient study case [ 33 ], one was an epidemiological study that assessed exposure to insect allergens by skin pricks [ 34 ], and three were cross-reactivity studies involving patients’ sera exposure to extracts containing insects’ allergens [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nine RCT studies were divided according to the primary outcomes studied: iron absorption [ 31 ], amino acid absorption and muscle protein synthesis or strength [ 25 , 26 , 28 ], amino acid absorption and appetite regulation [ 29 , 30 , 32 ], microbiota [ 24 ], and disease treatment, specifically, Chronic Obstructive Pulmonary Disease (CPOD) [ 27 ] ( Table 1 ). Six studies presented a high risk of bias, one had some concerns, and two studies had a low risk of bias ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%